The Significance of Gray Hair "Shayb" in Arabic Literature: A Study of the Life and Works of Al-Sharif Al-Radi - Kamarulzaman Abdul Ghani; Muhandis Azzuhri (Mesopotamian Journal of Arabic Language Studies, 2021)
Gray hair is a natural phenomenon that occurs in humans as they age. This phenomenon has gained significant importance in Arabic literature, as many consider it a sign of wisdom, experience, and dignity. This study examines the life and works of Al-Sharif Al-Radi, one of the greatest Arab poets of the Abbasid era, who lived in the fourth century AH. The study discusses the importance of gray hair in Al-Sharif Al-Radi's poetry and how he used this phenomenon in his poems to highlight the meanings of wisdom, experience, and dignity. The study also analyzes some of Al-Sharif Al-Radi's poems that address this topic and demonstrate the importance of gray hair in Arabic literature. Thus, the study sheds light on the significance of this phenomenon in Arabic literature and how it represents a symbol of wisdom, experience, and dignity in Arab culture.